The effect of eye exercise on eye fatigue in information technology study program students at the Muhammadiyah University of North Sumatra - Widyawati, Widyawati; Nurhaida, Nurhaida; Sihotang, Havija; Lubis, Elvi Susanti; Apriani, Riny; Hutauruk, Puput Melati; Syahna , Syahfira Ananda; Ardiansyah, Ardiansyah (Science Midwifery, 2025)
In the world of lectures, the use of computers is very popular among students, because computers help with assignments, search for information, communicate and others. However, if the use of computers is carried out for a long period of time, it will cause tension in the eye muscles, which can cause eye fatigue. Efforts to prevent eye fatigue are by doing eye exercise movements to improve the ability of the nerves and eye muscles. This study aims to analyze the difference in the mean value of eye fatigue between the treatment group and the control group towards reducing the level of eye fatigue in students of the Information Technology Study Program at the Muhammadiyah University of North Sumatra. This study is an experimental study using a randomized pre-posttest control group design. The study was conducted at the Muhammadiyah University of North Sumatra. A sample of 30 people was randomly selected to select research subjects. The research subjects numbered 15 people in the treatment group who were given eye gymnastics and 15 people in the control group without being given eye gymnastics. The level of eye fatigue was measured using an eye fatigue questionnaire consisting of 9 questions about symptoms of eye fatigue. Data analysis used a paired t-test. The results showed that there was a significant difference in the mean eye fatigue in the treatment group. The difference test of the pre-test and post-test scores of the two groups also showed that there was a significant difference in scores of 2.13 with a p value of 0.00 in the treatment group (p <0.05), while the p value was 0.15 in the control group (p>0.05). This proves that eye exercise has an effect on reducing the level of eye fatigue in students. It is concluded that eye exercise can reduce the level of eye fatigue in students.